Dentine Hypersensitivity Advances in Diagnosis, Management, and Treatment - Gillam, David G.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2015)
This book provides wide-ranging information on the progress achieved in the diagnosis, treatment and management of dentine hypersensitivity during the past few years. Recent advances in research, including innovations in the development of desensitizing agents, are fully described, and detailed attention is paid to novel clinical approaches and potential future strategies in product development. Introductory chapters cover important aspects of physiology, prevalence and aetiology, and advances in diagnosis and in vitro testing techniques for dentine hypersensitivity are discussed. Dentine hypersensitivity is a troublesome clinical condition that continues to perplex the clinician despite the vast array of available treatments that have been formulated to resolve the problem. There continues to be under-reporting of the condition by clinicians and uncertainty over aetiology, diagnosis and effective management. This book will hopefully contribute in combating these deficiencies and assist the clinician in delivering optimal patient care.
The Statement of the Problem -- Dentine Physiology: A Key to the Understanding of the Problem -- The Prevalence of Dentine Hypersensitivity -- Aetiology and Clinical Features of Dentine Hypersensitivity -- Advances in the Diagnosis of Dentine Hypersensitivity -- Advances in In Vitro Testing Techniques for Dentine Hypersensitivity -- From Concept to Production: An Overview of the Development of Desensitizing Agents -- The Relevance of In Vivo Evaluation of Desensitizing Agents for Managing Dentine Hypersensitivity -- Novel Clinical Approaches for the Treatment of Dentine Hypersensitivity -- The Impact of Dentine Hypersensitivity on the Quality of Life -- Advances in the Management of the Patient with Dentine Hypersensitivity: Motivation and Prevention -- Future Strategies for the Development of Desensitising Products.
Keywords: Dentistry; Dentistry